PROTEIN AND PEPTIDE BASED DRUG DELIVERY: PHARMACEUTICAL APPROACHES - Patel, Namrata; Amresh Gupta, Amresh Gupta; Arpita Singh; Nitish Kumar; Mohd. Aqil Siddiqui (International Journal of Indigenous Herbs and Drugs, 2021)
Protein and peptide are last three decades therapeutic peptides and proteins have risen in prominence as potential drug of future. Polymers of protein consist of amino acids covalently linked by peptide bonds. Peptides are small proteins composed of up to a couple of dozen amino acids proteins are rapidly degraded by digestive enzymes. Till recently, injections remain the foremost common means for administering these protein and peptide drugs. In the other routes that have been tried with varying degrees of success are the oral, buccal, intranasal, pulmonary, transdermal, ocular and rectal. In this review, the aim is to specialise in the varied routes and approaches for delivery of Peptide and protein drugs. The Continuous efforts are focussed for formulation of this therapeutics into safe and effective delivery systems. In this review briefly describes the possible methods for the delivery of protein and peptide drugs through various routes.